Overview of Law Enforcement in Hungary, with Special Respect to Local Level Law Enforcement - Christián, László (Magyar Rendészet, 2017)
This study is to give a brief overview of Hungarian law enforcement, with special respect to local level law enforcement. The operation of centralised state police is influenced by a statistical approach, which is the reason why no capacity remains for serving local communities and dealing with local matters, in spite of a few improvements in the recent years. This void of general security could be filled by local governmental law enforcement. Local governmental law enforcement bodies are founded and financed by the municipalities, with more limited empowerment to enforce the law than that of the police.